Car Users Willingness to Change Travel Mode in Response to On-street Parking Pricing: A Case Study of Dhaka City - Rahman, Farzana; Halder, Steve Evan (Journal of Engineering Science, 2023)
Dhaka is facing severe on-street parking challenges as car ownership emerges. This situation has led traffic congestion not only in local roads but also in collector and arterial roads. Parking plays a significant function in the management of traffic and congestion. In Dhaka city most of the on-street parking spaces are free which persuades car users to park their car randomly. The objective of this research is to examine car users’ behavior if on-street parking pricing is implemented. A questionnaire survey was conducted in arterial, feeder (or collector) and in local roads at 16 locations in Dhaka city. Attention was drawn to confirm that the survey could deal with either professional drivers o r motorists driving their own car as respondents. A multinomial logistic regression model was developed by using the data collected from 500 respondents. Based on the analytical results along with in-depth on-site investigations it was found that the probability of changing mode due to on street parking pricing is insignificant. Result demonstrates that educational qualification is the most important variable for switching mode from car to other if on-street parking charge is applied. Most of the users whose parking is associated with education and work trips will not change their transport mode if on-street parking charge is put into operation. Those trips are most closely associated with travel in peak periods and largely responsible for congestion. Car users usually face difficulties to find space for parking. Journal of Engineering Science 13(2), 2022, 31-41